Disrupting the Flow of Perception-Action through Design. (December 2022) - Heft, Harry
It is usually a mark of good design when technologies and tools that mediate goal-directed action are such that the user's attentional focus is maintained on the intended ends of action rather than on the technologies and tools themselves. When the mediators become the focus, the continuity of goal-directed action is disrupted, and the flow of action can be re-directed. What then is the purpose of the projects designed by the RAAAF studio, as described by Rietveld, which seem to be intended to do both? Disruption of the continuity of goal-directed perception-action may prompt reflection about the circumstances at work, and in so doing provoke a transformation in habitual patterns of action and of thought. The project "The End of Sitting" is intended to remediate the adverse health effects of standard chair-dominated offices through an unconventional office landscape that prompts intermittent postural readjustments, boosting the levels of activity common in such settings. The project "Bunker 599" demonstrates that seemingly unremarkable features of the landscape can sometimes conceal aspects of culture's history, and that design can function to draw attention to a hidden and even vanishing history. Design can enrich an individual's sense of place in a stream of cultural history.